Hulul, Ittihad, dan Wahdat al-Wujud dalam Perbincangan Ulama Zahir dan Batin - Syamhudi, M. Hasyim (IAIN Ponorogo, 2013)
Abstract: When prophet Musa, prayed to Allah , he requested to be able to see Him directly. But when he was shown to a mountain , he saw the mountain blasted and crushed and he was thrown away and fainted. Allah is not to be seen physically (Sufi metaphysics and gnosis (al-ma’rifah, ‘irfan), because physical appearance we can see, sometimes, can make a bias to our perception and make our decision wrong.. To be close to Allah forever in such a way can not be easily reached not only because of limited abilities of our senses but also because all decision we have made are as the product of empirical, and descriptive rationality, while Allah is the most absolute existence of the Supreme Being. Thus, to be close to Allah through senses means to restrict His absolute Almighty God as the Supreme Being, to narrow His traits of God and to reduce His soul of absoluteness. However, it does not mean that to communicate with Allah (the experience of mystical union or direct communion with ultimate reality), is like to communicate in an empty tube, “.. In fact, there are many scholars of mysticism (Sufism) who can tell their spiritual experiences about the greatness and dignity of God through meditation and spiritual insight (Mujahadah, muqarabah, and muraqabah) where Islamic mysticism seeks to evaluate, contemplate and purify the human soul. Their spiritual experience in peace and harmony with God the Al-mighty is called hulul, ittihad and wahdat al-wujud. The differences of experience between both rational and intuitive reasoning causes human tragedy to the scholars of mysticism like al Hallaj, al-Suhrawardi, and Shekh Siti Jenar.. Actually, this conflict should not happen if each side could keep their emotion academically, and respect their differences each other. Why? Because this conflict, eventually, causes the development of Islamic science become stagnancy like today.